Baseline TP53 mutations in adults with SCD developing myeloid malignancy following hematopoietic cell transplantation - Ghannam, Jack Y.; Xu, Xin; Maric, Irina; Dillon, Laura; Li, Yuesheng; Hsieh, Matthew M.; Hourigan, Christopher S.; Fitzhugh, Courtney D. (Blood, 2020)
There is a Blood Commentary on this article in this issue.